2018
DOI: 10.3233/jad-171168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Education on Alzheimer’s Disease-Related Neuroimaging Biomarkers in Healthy Controls, and Participants with Mild Cognitive Impairment and Alzheimer’s Disease: A Cross-Sectional Study

Abstract: Our findings suggest that education may exert a protective effect on total brain volume in the MCI stage but not in HC or AD. Thus, education may play an important role in preventing the onset of dementia through brain reserve in MCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
1
19
1
2
Order By: Relevance
“…Studies have shown that good education and cultural background have a positive effect on the ability of concept formation, vocabulary expression, spatial structure perception and memory, while cultural restriction may contribute to a negative effect [40]. Highly educated people often have a high reserve of neurons [41]. The more people receive education, the better subjective initiative and ability to adapt to the external environment, which may stimulate brain cells [42].…”
Section: Clinical Risk Factors For Preoperative Cognitive Impairmentmentioning
confidence: 99%
“…Studies have shown that good education and cultural background have a positive effect on the ability of concept formation, vocabulary expression, spatial structure perception and memory, while cultural restriction may contribute to a negative effect [40]. Highly educated people often have a high reserve of neurons [41]. The more people receive education, the better subjective initiative and ability to adapt to the external environment, which may stimulate brain cells [42].…”
Section: Clinical Risk Factors For Preoperative Cognitive Impairmentmentioning
confidence: 99%
“…The evidence regarding the association between education and amyloid deposition has been more limited. A recent study using data from the Alzheimer’s Disease Neuroimaging Initiative found that education duration was not correlated with amyloid deposition[5]. Additionally, findings from the Epidemiological Clinicopathological Studies in Europe (EClipSE)[6] showed education was associated with lower likelihood of dementia at death and greater brain volume, but not associated to neurodegeneration or vascular pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this pattern was distinct from the sex effect, which was found in the head of the hippocampus, in which inward displacement was associated with low education and female sex. Education has often been considered an influential factor in cognitive performance and hippocampal volume or microstructure (Piras et al 2011) as well as a protective factor against mild cognitive impairment (Wada et al 2018) and AD dementia (Meng and D’Arcy 2012; Groot et al 2018). Gender inequality with regards to education is predictable since older women from our datasets were born in a socioeconomic period when they were less encouraged to pursue higher education than men (Permanyer and Boertien 2019).…”
Section: Discussionmentioning
confidence: 99%